2022
DOI: 10.1002/ana.26552
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolites Link Dietary Patterns to Stroke Risk

Abstract: Objective: While dietary intake is linked to stroke risk, surrogate markers that could inform personalized dietary interventions are lacking. We identified metabolites associated with diet patterns and incident stroke in a nested cohort from the REasons for Geographic and Racial Differences in Stroke (REGARDS) study. Methods: Levels of 162 metabolites were measured in baseline plasma from stroke cases (n = 1,198) and random controls (n = 904). We examined associations between metabolites and a plant-based diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The strengths of this study include the detailed phenotyping of both clinical characteristics and neuroimaging features. Furthermore, the method of metabolite measurement by our group, which uses a targeted metabolomic approach, allows the detection of metabolites with high sensitivity and specificity …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of this study include the detailed phenotyping of both clinical characteristics and neuroimaging features. Furthermore, the method of metabolite measurement by our group, which uses a targeted metabolomic approach, allows the detection of metabolites with high sensitivity and specificity …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the metabolite measurements were quality controlled and normalized across batches by including human pooled plasma samples at regular intervals of every 10 injections. All metabolite level values were rank-based inverse normal transformed before statistical analysis since they did not conform to a normal distribution …”
Section: Methodsmentioning
confidence: 99%
“…11 Moreover, we extended these findings to show that many of these metabolites provided a link between dietary patterns and the risk of stroke. 18 In this study, we found that the association with gluconic acid was specific to Black participants. There was no difference in gluconic acid between all Black and White participants, suggesting that there is not an intrinsic biological difference.…”
Section: Discussionmentioning
confidence: 54%
“…11 Moreover, we extended these findings to show that many of these metabolites provided a link between dietary patterns and the risk of stroke. 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation